A Numerical Model for Fluvial Transport of Subglacial Sediment. Issue 8 (20th August 2019) - Delaney, Ian; Werder, Mauro A.; Farinotti, Daniel
Abstract : Sediment discharge from glaciers impacts downstream aquatic habitats, hydropower operations, and river infrastructure. Since discharge of subglacial sediment will evolve in response to glacier retreat, estimating future subglacial sediment dynamics is of great relevance. To develop tools and methods to better constrain the responsible processes, we present a till dynamics model that accounts for limited sediment access coupled to a subglacial hydrology model to describe the evolution of a subglacial till layer over a glacier's longitudinal profile in one dimension. Synthetic simulations examining the effects of changing hydrology highlight the importance of properly constraining both the erosion of underlying bedrock and the subglacial sediment connectivity. This is because changes in hydrology alter the timing of peak sediment discharge but only marginally affect total sediment discharge once the subglacial sediment reservoir is exhausted. Model simulations for real‐world glaciers yield insights into the distribution of sediment along the glacier bed, including locations where sediments are deposited or exhausted. Comparison between model results and field data shows that total and peak sediment discharge, as well as interannual variability, can be captured with acceptable skill for periods ranging from hours to decades. The results from this model show that modeling subglacial sediment transport on decadal to subdaily scales is possible but requires processes such as bedrock erosion and sediment connectivity to be considered. Key Points: A numerical model for subglacial sediment transport is presented Constraining subglacial till connectivity and bedrock erosion is imperative to describing subglacial sediment discharge Model outputs can capture measured variations in subglacial sediment discharge with reasonable skill